ANALISIS PERAN STAKEHOLDER DALAM KEBIJAKAN SURAT TANDA REGISTRASI TENAGA KESEHATAN MASYARAKAT DI KOTA SEMARANG - Palawa Pangeran Hidayat Putra; Septo Pawelas Arso; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Health workers who would implementing the practice or profession task should be had a license from government. The license could be have registration certificate for health workers which had regulated by registration health workers policy. To succeed the implementation of that policy, the government needs a stakeholder. This study aims to analyze the role of stakeholder in certificate of registration for public health workers in Semarang City. This research used the qualitative method which stakeholder subject in certificate of registration policy. Stakeholder from that policy who identified is Faculty of Public Health Diponegoro University (FKM Undip), The Indonesian Public Health Association Central Java (IAKMI Jateng), Council of Health Workers Province Central Java (MTKP Jateng), and Public Health Workers. This research used the exploratory research to understanding the problem with analysis method. Analysis method in this research used the stakeholder analysis with the interest, importance and influence as a assessment analyze. From the mapping stakeholder importance and influence, FKM Undip, IAKMI Jateng and MTKP Jateng have a high imprtance and influence in that policy and they should collaborate with each stakeholder, they could be catogorized as a advocate who driving the policy. Health workers have a high importance but low influence and need a inform the policy benefit, and it could be categorized as a follower in the policy. Therefore, each stakeholder need to collaborate to gave a influence the benefit of policy, it would be each stakeholder can reach the goals from the certificate of registration policy.